ANGISTRONGYLUS CANTONENSIS AND ANCYLOSTOMA CANINUM DETECTION IN SNAILS OF SÃO PAULO CITY (2016-2017), BRAZIL. - ORICO, L. D.; BARBOSA, C. M.; LUCA, L. R.; SOARES, R. M.; GREGORI, F. (Ars Veterinaria, 2019)
Achatina fulica snails cause environmental problems and represent a public health hazard since it is a host in the life cycles of various parasites, among them, Angiostrongylus cantonensis and, less frequently, Ancylostoma caninum. We report the occurrence of Angistrongylus cantonensis, as well as the unexpected finding of Ancylostoma caninum, in a total of 936 specimens of Achatina fulica snails from different regions of São Paulo city, Brazil. Samples were divided into 492 pools which were screened for nematodes. If present, larvae were submitted to DNA extraction and PCR protocol targeting, the ITS-2 gene junction. From the 183 positive pools for larvae presence, 97 showed specific 650 bp band at electrophoresis and 21 presented bands nearly 300 bp. Two amplicons from each size were and sequenced. A BLAST/n of 650 bp sequences presented identity with Angistrongylus cantonensis, while the two of 300 bp, showed identity with Ancylostoma caninum, also supported by phylogenetic analysis. This is the second report of Ancylostoma caninum found in these snails in the world, therefore, this study allows a better understanding about these diseases and highlights the need of continue systematically mapping sites that can be infested with the mollusc.